Data borders : how Silicon Valley is building an industry around immigrants - Villa-Nicholas, Melissa (Oakland, California : University of California Press, 2023)
"Data Borders investigates entrenched and emerging borderland technology that ensnares all people in an intimate web of surveillance where data resides and defines citizenship. Detailing the new trend of biologically mapping undocumented people through biotechnologies, Melissa Villa-Nicholas shows how surreptitious monitoring of Latinx immigrants is the focus of and driving force behind Silicon Valley's growing industry within defense technology manufacturing. Villa-Nicholas reveals a murky network that gathers data on marginalized communities for purposes of exploitation and control that implicates law enforcement, Border Patrol, and ICE, but that also pulls in public workers and the general public, often without their knowledge or consent. Enriched by interviews of Latinx immigrants living in the borderlands who describe their daily use of technology and their caution around surveillance, this book argues that in order to move beyond a heavily surveilled state that dehumanizes both immigrants and citizens, we must first understand how our data is being collected, aggregated, correlated, and weaponized with artificial intelligence and then push for immigrant and citizen information privacy rights along the border and throughout the United States"--
Un pincel de Rapanzual -- Introduction -- The physical borderlands, the data borderland -- Latinx data bodies -- Networked : meet the new Migra -- The good citizen : citizen milieu -- The stories we tell : storytelling for data borders -- Pero queríamos norte -- First person parables : imagining borderlands and technologies -- Conclusion : esperanza, yet hope remains.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 19, 2023).
JSTOR
Keywords: Latin Americans -- Mexican-American Border Region -- Social conditions -- 21st century; Immigrants -- Mexican-American Border Region -- Social conditions -- 21st century; Electronic surveillance -- Mexican-American Border Region -- 21st century; Latino-Américains -- Région frontalière mexicano-américaine -- Conditions sociales -- 21e siècle.; Surveillance électronique -- Région frontalière mexicano-américaine -- 21e siècle.; SOCIAL SCIENCE / Technology Studies; Electronic surveillance; Immigrants -- Social conditions; Latin Americans -- Social conditions; North America -- Mexican-American Border Region; 2000-2099